Photothermal magnetic Janus fabric vs cast membranes and their application in solar-based desalination - Norhan Nady; Nourhan Rashad; Noha Salem; Marwa Showman; Mohamed R. Elmarghany; Mohamed Salem; Ahmed M. Hamed; Sherif. H. Kandil (Applied Water Science, 2025)
Abstract Water shortage poses a significant global challenge, and there is a pressing need for effective and sustainable desalination technologies that do not require brine disposal. In this study, we fabricated fiber membranes using a mixture of poly(vinylidene fluoride)-co-hexafluoropropylene (PcH) and poly(ethersulfone) (PES) polymers, incorporating black magnetic iron-nickel alloy nanoparticles at high molar ratios of Ni to Fe (90:10 and 80:20). The nanoparticles were integrated into the PcH/PES blend in two ways: (1) as a coating layer on the prepared fibers, and (2) both as a coating layer and dispersed within the PcH/PES polymer dope. The resulting fiber membranes were analyzed using various techniques, and their solar absorption capacity was assessed. This innovative approach of incorporating black magnetic iron-nickel alloy nanoparticles as photothermal agents into electrospun polymer fiber membranes was compared to our previous work on cast membranes made from the same iron-nickel/PcH/PES composite dope. This study reinforces the idea that increased thickness of the cast membranes can enable them to function as 3D blocks, enhancing solar heat concentration and, in turn, boosting the water evaporation rate. This study highlights our ongoing efforts to develop advanced materials and designs for effective solar-driven membrane distillation technology.